Population census and age category character of Stump-tailed macaque, Macaca arctoides, in Northern Peninsular Malaysia - SYAMIL ABD RAHMAN; MOHD-RIDWAN ABD RAHMAN; AMSAH MOHD ARIF; MUHAMMAD ABDUL-LATIFF ABU BAKAR; BADRUL MUNIR MD ZAIN (Society for Indonesian Biodiversity, 2019)
Abstract. Syamil AR, Mohd-Ridwan AR, Amsah MA, Abdul-Latiff MAB, Md-Zain BM. 2019. Population census and age category character of Stump-tailed macaque, Macaca arctoides, in Northern Peninsular Malaysia. Biodiversitas 20: 2446-2452. Macaca arctoides is reported to be distributed only in the northern part of Malay Peninsula. Intensive scientific observations have never been carried out before on this neglected macaque in the northern range. Thus, in this article, an estimation of population data on the Malaysian stump-tailed macaques that were found in Wang Kelian forest areas in Perlis State Park, Malaysia is presented. Intensive field observations were conducted from Sept 2018 to January 2019 with scanning sampling. The study revealed a total of 171-176 stump-tailed macaques, consisting of 44 (25%) adult males, 28 (16%) adult females, 19-22 (11%) sub-adult males, 16-19 (10%) sub-adult females, 43 (25%) juveniles, and 21-23 (13%) infants. Two main groups were observed, which were the Nomad and the Batat groups. Their ranging areas appear to sometimes overlap each other, while some Nomad members were observed in the Batat group. The age structure can be differentiated through body size and pelage coloration. The stump-tailed macaque populations in Wang Kelian are sensitive to human presence, while their habitat area is threatened by human illegal poaching activities. More conservation efforts are needed to conserve this neglected macaque from local extinction.